2017
DOI: 10.1080/09658211.2017.1349804
|View full text |Cite
|
Sign up to set email alerts
|

The Hopkins Verbal Learning Test: an in-depth analysis of recall patterns

Abstract: One of the earliest signs of dementia is memory issues and verbal word lists, such as the Hopkins Verbal Learning Test (HVLT), are successfully used for screening. To gain insight in how memory is affected in dementia, and to further improve the efficacy of the HVLT, in-depth analysis of the recall patterns of dementia cases and controls was conducted. Dementia cases and controls were matched for factors that can affect performance, such as age, gender and education level. Word frequency, syllable length, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…Memory recall was assessed using the word list component of the Hopkins Verbal Learning Test (Grenfell‐Essam et al., 2018). Participants read word lists from the Hopkins Verbal Learning Test at the rate of one word every 2 s in a supine position prior to 3 hr of sitting.…”
Section: Methodsmentioning
confidence: 99%
“…Memory recall was assessed using the word list component of the Hopkins Verbal Learning Test (Grenfell‐Essam et al., 2018). Participants read word lists from the Hopkins Verbal Learning Test at the rate of one word every 2 s in a supine position prior to 3 hr of sitting.…”
Section: Methodsmentioning
confidence: 99%
“…One study (Riekkinen et al, 1998) compared recency effects in individuals with AD who were either "responders" or "non-responders" to an administration of a cholinesterase inhibitor, Tetrahydroaminoacridine, and was not included in the current review. Two other studies (Grenfell-Essam, Hogervorst, & Rahardjo, 2018;Jones, Greer, & Cox, 2011) utilized archival data in which patients were diagnosed with or without dementia, but were not included in the current review due to lack of specificity regarding diagnosis (i.e., AD, MCI, or another type of dementia). A complete list of reviewed studies and their findings can be found in Supplemental Table S1.…”
Section: Search Strategymentioning
confidence: 99%
“…In a series of memory tests, we utilized HVLT to study age differences in memory function. The HVLT makes for an appealing measure because it provides a more detailed and standardized assessment of verbal memory than briefer tasks (28). Our results indicate that older adults manifest deficits in immediate memory recall and delayed memory recall.…”
Section: Associations Between Memory and Cerebellar Lobulesmentioning
confidence: 68%
“…Previous task functional magnetic resonance imaging (fMRI) studies have also shown that different cerebellar subregions participate in processes of encoding, preservation, and retrieval output of WM (7,24,25). However, notably, unlike the cerebral cortex, in which earlier damage allows for compensatory plasticity (26), cerebellar damage earlier in life can result in worse cognitive outcomes (27), leading to longterm deficits (27,28).…”
Section: Introductionmentioning
confidence: 99%